DEVELOPMENT OF THE EMOTIONAL AND VOLITIONAL STABILITY OF A MARINE SPECIALIST IN MULTICULTURAL ENVIRONMENT - Vera F. Tenishcheva; Elena N. Tsyganko; Yuliya S. Kuznetsova (Вестник Северо-Кавказского федерального университета, 2022)
Integrative context approach to marine specialist training has been analyzed in the article. A scheme of relationship of educational models, organizational forms and technical training means for acquisition of pro- fessional typical tasks in multicultural environment has been developed.